2009
DOI: 10.1099/vir.0.005025-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the zinc-finger and basic motifs of chrysanthemum virus B p12 protein in nucleic acid binding, protein localization and induction of a hypersensitive response upon expression from a viral vector

Abstract: The genomes of carlaviruses encode cysteine-rich proteins (CRPs) of unknown function. The 12 kDa CRP of chrysanthemum virus B (CVB), p12, has been shown previously to induce a hypersensitive response (HR) when expressed from potato virus X (PVX). This study demonstrated that a p12-induced HR was preceded by induction of a number of genes related to pathogenesis, stress and systemic acquired resistance. p12 localized predominantly to the nucleus. Interestingly, it was found that p12 bound both RNA and DNA in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 52 publications
(50 reference statements)
3
44
0
Order By: Relevance
“…Recently, we found that the p12 protein of chrysanthemum virus B (CVB) is implicated in host gene induction as a pathogenicity and virulence determinant (Lukhovitskaya et al, 2009). CVB belongs to the genus Carlavirus, which comprises 35 definitive species and 29 tentative members with conserved genome organization (Levay and Zavriev, 1991;Adams et al, 2004;Martelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we found that the p12 protein of chrysanthemum virus B (CVB) is implicated in host gene induction as a pathogenicity and virulence determinant (Lukhovitskaya et al, 2009). CVB belongs to the genus Carlavirus, which comprises 35 definitive species and 29 tentative members with conserved genome organization (Levay and Zavriev, 1991;Adams et al, 2004;Martelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Their positive-stranded genomic RNA encodes six genes, of which the gene for p12 occupies the extreme 39-terminal position (see Supplemental Figure 1A online; Adams et al, 2004;Martelli et al, 2007). CVB p12 and its homologs in other carlaviruses are Cys-rich proteins characterized by a central C-4 type zinc finger defined by its RCxRCxRxxPx 6-8 CDxxxC motif and an adjacent nuclear localization signal (NLS; see Supplemental Figure 1C online; Gramstat et al, 1990;Koonin et al, 1991;Lukhovitskaya et al, 2009; note that the carlavirus C-4 superfamily should not be confused with the C4 proteins of geminiviruses). The p12 protein binds both RNA and DNA but exhibits a preference for DNA in the presence of Zn 2+ and its pathogenic effects depend on translocation into the nucleus (Gramstat et al, 1990;Lukhovitskaya et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 3,4 The ectopic expression of upp-L in the leaves results in cell proliferation and tissue growth phenotypically manifested as severe leaf malformation, the developmental alterations similar to the symptoms induced by CVB infection in the host species. The asymmetric changes in the expression pattern of key cell-cycle regulators (downregulation of cell-division inhibiting E2FC TF and upregulation of cell proliferation promoting E2FB) suggest that upp-L acts upstream of the core cell-cycle regulators conserved between animals and plants.…”
Section: R Ecent Studies Have Uncovered Numerousmentioning
confidence: 99%